The Influence of information quality, risk perception, and promotion on buying decision at Tokopedia on Mikroskil University students - Fenny Septiani; Ella Silvana Ginting; Suci Pertiwi (LLDIKTI Wilayah 1 Sumatera Utara, 2022)
The purpose of this study was to determine and analyze the influence information quality, risk perception, and promotion on buying decision at Tokopedia on Mikroskil University students. The type of this research used in this study was quantitative research with descriptive approach. The population of this research were students of Mikroskil university, faculty business amounted 162 respondents. The sampling technique was using a saturated sample and the number of samples in this study amounted 162 respondents. The method of data analysis used multiple linier regression analysis. The results showed that the information quality, risk perception, and promotion variables partially influence the buying decision at Tokopedia on Mikroskil University Students. However, simultaneously variables, information quality, risk perception, and promotion affect buying decision at Tokopedia on Mikroskil University Students. The results of the coefficient of determination is 82,3%, this shows that the variables consisting of information quality, risk perception, and promotion affect the buying decision variables by 82,3%. While the remaining 17,7% is explained by other variables not explained in this study.